Reduced procedural motor learning in deaf individuals - Lévesque, Justine; Théoret, Hugo; Champoux, François (Frontiers in Human Neuroscience, 2014)
Studies in the deaf suggest that cross-modal neuroplastic changes may vary across modalities. Only a handful of studies have examined motor capacities in the profoundly deaf. These studies suggest the presence of deficits in manual dexterity and delays in movement production. As of yet, the ability to learn complex sequential motor patterns has not been explored in deaf populations. The aim of the present study was to investigate the procedural learning skills of deaf adults. A serial reaction-time task (SRTT) was performed by 18 deaf subjects and 18 matched controls to investigate possible motor alteration subsequent to auditory deprivation. Deaf participants had various degrees of hearing loss. Half of the experimental group were early-deaf adults mostly using hearing aids, the remaining half were late-deaf adults using a cochlear implant. Participants carried out a repeating 12-item sequence of key presses along with random blocks containing no repeating sequence. Non-specific and sequence-specific learning was analyzed in relation to individual features related to the hearing loss. The results revealed significant differences between groups in sequence-specific learning, with deaf subjects being less efficient than controls in acquiring sequence-specific knowledge. We interpret the results in light of cross-modal plasticity and the auditory scaffolding hypothesis.